The aging self: how older men and women reflect on themselves and others - Paź, Marta; Nowicka, Anna (Frontiers in Aging Neuroscience, 2025)
ObjectivesSelf-relevant stimuli, such as one’s name or face, are prioritised by the brain, leading to faster responses and enhanced attentional processes. The psychophysiological underpinnings of those mechanisms are related to early and late event-related potential (ERP) components, particularly to reduced N2 and enhanced late positive potential (LPP). However, most up-to-date research on the self has focused on groups of young adults while older groups were rarely recruited for such experiments — the present study aimed to fill this gap. Thus, age-related changes in the self-referential processing were investigated and plausible gender differences were explored.MethodsEEG data were collected from 56 participants over 60 years old. Before the experiment, participants completed psychological assessments and selected a close person (e.g., a friend) and a preferred Polish celebrity (e.g., Lech Wałęsa). The experimental task consisted of three blocks (Self, Close, Famous), where participants were viewing 150 adjectives and judged whether each adjective applied to the description of the assigned person.ResultsERP results indicated higher LPP amplitudes and reduced negative N2 components in the self condition in comparison both to the close as well as famous person conditions. Notably, these effects seem to be more pronounced in older women.DiscussionEnhanced LPP indicates deeper self-reflection linked to the highest attention allocation to self-related personality traits. On the other hand, reduced N2 suggests lower involvement of executive control in visual encoding and response execution. In conclusion, the findings of our study revealed a robust self-prioritization effect in older adults, driven primarily by women.